Aging, not age-associated inflammation, determines blood pressure and endothelial responses to acute inflammation. Issue 12 (December 2016) - Lane-Cordova, Abbi D.; Ranadive, Sushant M.; Kappus, Rebecca M.; Cook, Marc D.; Phillips, Shane A.; Woods, Jeffrey A.; Wilund, Kenneth R.; Baynard, Tracy; Fernhall, Bo
Abstract : Background: Aging is characterized by a state of chronic, low-grade inflammation that impairs vascular function. Acute inflammation causes additional decrements in vascular function, but these responses are not uniform in older compared with younger adults. We sought to determine if older adults with low levels of baseline inflammation respond to acute inflammation in a manner similar to younger adults. We hypothesized age-related differences in the vascular responses to acute inflammation, but that older adults with low baseline inflammation would respond similarly to younger adults. Method: Inflammation was induced with an influenza vaccine in 96 participants [older = 67 total, 38 with baseline C-reactive protein (CRP) > 1.5 mg/l and 29 with CRP < 1.5 mg/l; younger = 29]; serum inflammatory markers IL-6 and CRP, blood pressure and flow-mediated dilation (FMD) were measured 24 and 48 h later. Results: Younger adults increased IL-6 and CRP more than the collective older adult group and increased pulse pressure, whereas older adults decreased SBP and reduced pulse pressure. The entire cohort decreased FMD from 11.3 ± 0.8 to 8.3 ± 0.7 to 8.7 ± 0.7% in younger and from 5.8 ± 0.3 to 5.0 ± 0.4 to 4.7 ± 0.4% in older adults, P less than 0.05 for main effect. Older adult groups with differing baseline CRP had the same IL-6, blood pressure, and FMD response to acute inflammation, P less than 0.05 for all interactions, but the low-CRP group increased CRP at 24 and 48 h (from 0.5 ± 0.1 to 1.4 ± 0.2 to 1.7 ± 0.3 mg/l), whereas the high-CRP group did not (from 4.8 ± 0.5 to 5.4 ± 0.5 to 5.4 ± 0.6 mg/l), P less than 0.001 for interaction. Conclusion: Aging, not age-related chronic, low-grade inflammation, determines the vascular responses to acute inflammation.